Analysis and Identification of Trihalomethanes in Lisbon Indoor Swimming Pools: Distribution, Determinants and Human Exposure - Silva, Z. (2012)
Water disinfection methods are used in swimming pools to ensure an effective protection of users against microbiological pathogens, being chlorination the most common disinfection method used worldwide. The use of chlorine based treatment techniques has one strong drawback, which is the generation of disinfection by-products (DBPs), potentially harmful products that have been associated with respiratory and ocular symptoms, bladder cancer and adverse reproductive effects. Amongst DBPs, the most better characterized are trihalomethanes (THMs): chloroform (CF), bromoform (BF), bromodichloromethane (BDCM), and chlorodibromomethane (DBCM). In Portugal a specific legislation to assess the quality of swimming pools is inexistent. The guideline value used to evaluate total THMs in water (TTHMsW) is the one established in the Law 306/2007 - 100 μg/L. Some other water/air parameters were assessed by Law 5/97, WHO guidelines for safe recreational water environments (2006) and Standard 62.1 (2006) from American Society of Heating, Refrigerating, and Air-Conditioning Engineers (ASRHAE). The main goal of this investigation was to study the occurrence, distribution and determinants of THMs in indoor swimming pools. This will also enable an evaluation of the exposure of users to THMs. In order to achieve this goals, the characterization of water quality in 30 Lisbon indoor swimming pools, using chorine based treatment techniques, was made during a six month period. Several parameters such as TTHMs, CF, BDCM, DBCM, BF levels in water, free residual chlorine (FrCl), pH, TW, Tair, Hu, chemical oxygen demand (COD), and other, were determined in each pool, once a month. Statistical analysis was performed using the SPSS 17.0 software. Descriptive analysis was applied to all variables. Student’s t-test, Mann-Whitney tests and Spearman’s rank correlation coefficient were also used. Large variation in TTHMs and CF water levels between the pools was obtained, being CF the THM obtained in higher concentrations, with sporadic higher values than the allowed. In air, CF level (CFair) also presented occasional higher levels. There was a clear positive linear correlation between CFW and TTHMsW (R>0.95, p<0.01), CFW and CFair (R> 0.5; p<0.05), CFW and FrCl (R>0.2; p<0.05) and, CFw and Tw (R>0.2; p<0.05). Good correlations were also obtained between other THMs: BDCM and DBCM (R>0.5, p<0.01) and BF and DBCM (R>0.6; p<0.05). The strong positive correlation obtained between CFW and TTHMsW was expected, since, usually, CFW has the higher contribution to TTHMsW. CFW is often considered as a good indicator of TTHMs concentration in water. Therefore correlations between TTHMs and CFair, FrCl, and Tw were expected and observed: TTHMsW vs CFair (R>0.5; p<0.05), TTHMsW vs FrCl (R>0.2; p<0.05) and TTHMsW vs TW (R>0.2; p<0.01). In conclusion, reasonable water and air quality was obtained in the studied Lisbon swimming pools, although some pools presented high TTHMsW, CFW and CFair. These results clearly demonstrate that THMs monitoring is particularly important and that, in a near future, this should be extended to other DBPs. Furthermore, for conscious use of swimming pools, appropriate and targeted information about safe practices should be provided to pool users.